2022
DOI: 10.1002/zaac.202200216
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis and crystal structure evaluation of Na2ZnSnS4

Abstract: Phase‐pure and highly crystalline Na2ZnSnS4 was prepared via a mechanochemical synthesis route. It crystallizes in the kesterite‐type structure. The unusual large Debye‐Waller factors of the sodium atoms were analyzed in detail, respecting also group‐theoretical aspects. The results point to the existence of static disorder, mainly to the presence of various patterns of sodium ordering on a local scale. This is confirmed by quantum‐chemical calculations at hybrid density‐functional theory level. The dynamic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…SCXRD revealed that BaCu 2 SiS 4 crystallizes in the trigonal, noncentrosymmetric, and chiral space group P3 2 21. The threedimensional structure consists of corner-sharing [CuS 4 ] and [SiS 4 ] tetrahedra that propagate as a helix, creating channels along the [100], [010], and [110] directions (Figure 2). Ba atoms are located in these channels.…”
Section: Resultsmentioning
confidence: 99%
“…SCXRD revealed that BaCu 2 SiS 4 crystallizes in the trigonal, noncentrosymmetric, and chiral space group P3 2 21. The threedimensional structure consists of corner-sharing [CuS 4 ] and [SiS 4 ] tetrahedra that propagate as a helix, creating channels along the [100], [010], and [110] directions (Figure 2). Ba atoms are located in these channels.…”
Section: Resultsmentioning
confidence: 99%